Mencari Tolok Ukur Eksistensi Hak Ulayat atas Tanah Menurut UUD 45 - Winahyu Erwiningsih (Jurnal Hukum IUS QUIA IUSTUM, 2003)
Democracy highly upholds respective principle of customary law society in general and traditional indegenous agrarian rights in particular. This principle should be elaborated firmily in regulations in order to avoid power abuse inward customary law community. Local government should not hesitate to provide traditional indegenous agrarian rights in listed form to avoid consession objectivism offorest management by private sector. Local govemment should also had courage to initate the establishement of custom deliberation institution as its partner and seek mutual benefited solution when public interests of traditional indigenous soil use as development object.